AN ANALYSYS OF DEIXIS IN THE ARTICLE OF THE JAKARTA POST - NitaBonita Samosir; Zainuddin Zainuddin (State University of Medan, 2013)
ABSTRACT This thesis deals with the English deixis. The objectives of this study are to analyze type of deixis and to find out the most dominant type of deixis in the political article of Jakarta Post. This study was conducted by using descriptive quantitative design. The source of data was taken from the article of Jakarta Post and five articles are taken as the samples. Documentary technique is used in collecting data. The findings showed that there are five types of deixis found in The Jakarta Post article, namely Person deixis, 99 times occur (42,85%), Place deixis, 8 times occur (3,46%), Time deixis 43 times occur (18,61%), Discourse deixis 42 times occur (18,18), and the last is social deixis 39 times occur (16,88%). From the analysis from deixis is the most types of The Jakarta Post can be found. So it can be said that The Jakarta Post tends to use person deixis as the dominant type compound an another types. This is because The Jakarta Post the news mostly dealt with the person interaction. Keywords: deixis, newspapers, The Jakarta Post, documentary, descriptive qualitative